New associations: INFG and TGFB1 genes and the inhibitor development in severe haemophilia A. (30th April 2015) - de Alencar, J. B.; Macedo, L. C.; de Barros, M. F.; Rodrigues, C.; Shinzato, A. H.; Pelissari, C. B.; Machado, J.; Sell, A. M.; Visentainer, J. E. L.
<x xml:space="preserve">Abstract</x> Introduction The development of factor VIII (FVIII) inhibitor is the main complication of replacement therapy in patients with haemophilia A (HA). A ratio of 5–7% of individuals HA develops antibodies (inhibitors) against the FVIII infused during the treatment, thereby reducing their pro‐coagulant activity. The immunomodulatory cytokine genes have been related to the risk of development of alloantibodies in several studies, mainly in HA with severe form. Aim We investigated the polymorphisms in regulatory regions of cytokine genes (IL1A, IL1B, IL1R, IL1RA, IL4RA, IL12, INFG, TGFB1, TNF, IL2, IL4, IL6, IL10) that could influence the risk of developing inhibitors in patients with severe HA. Methods The genotyping of cytokine genes of 117 patients with HA was performed by polymerase chain reaction with sequence‐specific primers (PCR‐SSP) using the protocol recommended by the manufacturer (Invitrogen kit Cytokines®, Canoga Park, USA) Results From the cohort of 117 patients with severe HA, 35 developed inhibitors. There was a higher frequency of +874 T allele in INFG and of +869 TT and TG/TG in TGFB1 genes on patients with inhibitors. Conclusion This suggests that polymorphisms in INFG and in TGFB1 genes are related to risk of developing inhibitor, and could contribute to a genetic profile of the individual HA for the risk of inhibitors development to FVIII.